TRANSFORMATIVE APPROACH AS THE KEY TO 21ST-CENTURY EDUCATIONAL INNOVATION - Hasna Zhafirah Ramadhani; Hasna Zhafirah Ramadhani; Azmy Haidar Hakim; Mufidah Nur Amalia; Ummi Masrufah Maulidiyah; Qonita Az Zanro (P3I UMSurabaya, 2025)
The 21st century requires an education system that transcends knowledge transmission and fosters deep personal transformation. The main challenge lies in bridging the gap between traditional rote-based education and the growing demand for adaptive and innovative thinkers. This study explores Transformative Education as a crucial framework for developing holistic individuals who are critical, creative, collaborative, and adaptive, true Innovative Humanists. The significance of this topic lies in its capacity to empower learners as global change agents. It hypothesizes that a transformative approach, where teachers act as catalysts and learning becomes an authentic process of discovery, effectively cultivates strong character and innovation readiness. Employing case studies, qualitative-descriptive methods, and field surveys, this research aims to identify best practices and their impact. Ultimately, transformative education serves as both an ethical and strategic imperative to ensure future generations are not only intellectually capable but also humane, reflective, and socially responsible.